The right to food security in a changing Arctic: the Nunavut Food Security Coalition and the Feeding My Family campaign. : A New Dialogue: Putting People at the Heart of Global Development. Conference Report from the Hunger, Nutrition and Climate Justice Conference. April 15-16 2013. - Papatsie, Lessee; Ellsworth, Leanna; Meakin, Stephanie; Kurvits, Tiina (Irish Aid, Mary Robinson Foundation: Climate Justice CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and World Food Programme., 2013)
In Nunavut in the Canadian Arctic, Inuit are mobilising themselves and their government to address rising food prices and food insecurity; focusing on the right to a traditional way of life and the challenges brought by climate change and industrialisation.